LIMNOLOGICAL STUDIES IN RELATION TO PHYTOPLANKTONS OF RIVER WARDHA NEAR EKONA, TALUKA WARORA, DISTRICT CHANDRAPUR, MAHARASHTRA STATE, INDIA - P.R. Makde,; M. C. Kale, (The Bioscan, 2025)
Over a one year period, this study examined the whole impact of coal mines and power plants on entertained local phytoplankton community and physico-chemical characteristics of Wardha river near Ekona. These characteristics were studied for a period of 12 months from February 2022 – January 2023. In view of above, an attempt was made to study certain limnological parameters such as water temperature, conductivity, T.D.S., turbidity, pH, D.O., total alkalinity, B.O.D., free CO2, chloride, phosphate and nitrate. For examination of above all mentioned parameters American Public Health Association (APHA - 1985), American Water Works Association was made. Present research work concludes that Wardha river near Ekona was basically for irrigation purpose is now polluted water body due to continuous discharge of coal mines and power plants.